Selection In vitro of Granola Potato M1 Againts Bacteria Wilt Disease Ralstonia solanacearum - Asta, Hidayat; Wardiyati, Tatik; Maghfoer, Mochamad Dawam (Journal of Tropical Plant Protection, 2012)
AbstracBacterial wilt disease caused by Ralstonia solanacearum is an important disease and could decreased yield up to 80%. Generally, bacterial disease is more difficult to control than other diseases. Moreover, there are no chemicals that can be used to control this pathogen. The approach through genetic improvement by using Ethyl Methane Sulfonate and in vitro selection are procesess to generate variants resistant against bacterial wilt on potato plants. Granola potato M1 is the result of treatment with mutagen Ethyl Methane Sulfonate.Â Based on the results of selection in vitro of potato plantlets M1 Granola with suspense of Rs 9 Ã 1010 CFU / ml, were can be induced E9 three potato plantlets are rather susceptible toÂ  Ralstonia solanacearum through the regenerated node and E6 and E8 treatment can be induced moderately resistant planlets against Ralstonia solanacearum.Â Keyword: EMS, Granola, Ralstonia solanacearum